Treatment and Outcome of Stiff-Man Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Neurologists at the Mayo Clinic, Rochester, MN extended their reports of patients with stiff-man syndrome (SMS), first reported there by Drs Moersch and Woltman in 1956.